2021
DOI: 10.31219/osf.io/sdntr
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Use of Ai (Artificial Intelligence) in English Learning Among University Student: Case Study in English Department, Universitas Airlangga

Abstract: Aim: This research aim is to analyze an artificial intelligence platform that can be used in imparting education as well as evaluating student performance. Method: This research was conducted with a qualitative method by conducting in-depth interviews and a literature study. Results: The findings of this study shows that Artificial Intelligence technology can be used as a means of developing English learning for students. Discussion: There have been several studies that support research results, that AI can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…However, these methods of teaching and learning English were used extremely infrequently. Dewi et al (2021) concluded that AI could play roles beyond conversational possibilities, such as motivating, guiding, and providing feedback for language development.…”
mentioning
confidence: 99%
“…However, these methods of teaching and learning English were used extremely infrequently. Dewi et al (2021) concluded that AI could play roles beyond conversational possibilities, such as motivating, guiding, and providing feedback for language development.…”
mentioning
confidence: 99%